2022
DOI: 10.3126/kumj.v20i1.49896
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Tear at Knee: Repair or Resect? An Early Experience from a University Hospital in Nepal

Abstract: Background The meniscus plays an important role in maintaining healthy articular cartilage. Meniscus tear, one of the common intra-articular knee lesions, is treated by either debridement or repair. Objective This study aims at identifying the early outcome of meniscus tears treated by debridement or repair. This study also elaborates on the spectrum of meniscal injuries presented in a tertiary care hospital in Nepal. Method A retrospective descriptive cross-sectional study was conducted at Orthope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 10 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…Seven studies were multiple publications reporting on the same training course or study cohort and therefore are reported with their parent study to avoid duplication, resulting in 45 unique studies (Fig. 1) [12–63]. Descriptions of included studies can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies were multiple publications reporting on the same training course or study cohort and therefore are reported with their parent study to avoid duplication, resulting in 45 unique studies (Fig. 1) [12–63]. Descriptions of included studies can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Stein et al [87], Shelbourne et al [81], and Hoshino et al [36] reported tears in the red–red and red–white zones, whereas ruptures in the white–white zones underwent partial meniscectomy. The remaining studies do not describe in detail the tear location in relation to the vascular zones [12, 17, 23, 25, 45, 46, 82–85, 88, 92]. Although removal or partial resection of the meniscus is preferred for tears located in the less vascularised zones, there are increasing reports of successful repairs in the critical zones as well [18, 77].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current studies are retrospective [17, 24, 45, 49, 50, 81–83, 88, 92]. Level I studies are completely missing, only four have an evidence level of II [36, 71, 75, 81], and 80% (16 of 20) of the included studies achieve level III evidence [12, 17, 23, 24, 45, 46, 49, 50, 76, 82–85, 87, 88, 92]. Further long‐term high‐quality studies considering the limitations mentioned above are needed to confirm the advantage of meniscal repair over resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further three months were required for data extraction, checking and harmonisation before analyses commencement. In this timeframe, only one additional IA glucocorticoid/placebo randomised trial was published [ 50 ]. This highlights the acquisition of data in an IPD analysis being a time-consuming and resource-intensive process.…”
Section: Discussionmentioning
confidence: 99%